189. Evaluating the Impact of Mandatory Indications on Antibiotic Utilization: A Retrospective Study. (26th November 2018) - Chan, April Jane; Downing, Mark; Langford, Bradley
Abstract: Background: Mandatory indications for antimicrobial agents are recommended by a number of organizations to act as a force function, requiring prescribers to provide a reason for prescribing at the time of order entry. We evaluated the impact of introducing a mandatory indication field into electronic order entry for selected antibiotics on utilization of antibiotics at a large community hospital in the context of an established antimicrobial stewardship program. Methods: A descriptive analysis of the mandatory indication fields for the study antibiotics (intravenous and enteral clindamycin, ciprofloxacin, metronidazole, moxifloxacin, and vancomycin) for adult patients 18 years and above for 1-year (December 1, 2015–November 30, 2016) postimplementation was conducted. An independent t -test was used to measure the primary outcome of change in drug utilization of study and control antibiotics before (6 months pre) and after (12 months post) the initiation of mandatory indications. Drug utilization was calculated as days of therapy (DOT)/1, 000 patient-days for both the study and control antibiotics individually and as a group. Oral amoxicillin/clavulanate and intravenous piperacillin/tazobactam orders which have no mandatory indications were used to examine any associated shifts in antibiotic utilization. Results: A total of 8, 399 orders were evaluated in the 1-year post-implementation period; of which, 4, 572 were for study antibiotics. The preset mandatory indications were selected 30–55% of the time. For the primary outcome, there was a statistically significant decrease in DOT/1, 000 patient-days for study antibiotics as a group pre- and postintervention (mean 100 vs. 82, P = 0.024) as but not individually. However, there was a statistically significant increase in DOT/1, 000 patient-days for the control antibiotics (mean 78 vs. 91, P = 0.01), driven by the increase in piperacillin/tazobactam utilization. Conclusion: This study showed the moderate use of preset mandatory indications which suggests that the preset list of indications can be optimized. Furthermore, mandatory indications were shown to be associated with a reduction in study antibiotics utilization but may lead to shifts in usage to other nonstudy antibiotics. Disclosures: All authors: No reported disclosures.